Gender Disparities and Their Impact on the Professional Experiences of Female Neurosurgery Residents in Germany: A Cross-Sectional Survey (2024)
Despite advancements in gender equality within neurosurgery, the field continues to encounter challenges related to the under-representation of women and reports of gender-based disparities. This study examines the impact of these disparities on the experiences, professional development, and well-being of female neurosurgery residents in Germany, identifying specific challenges within the neurosurgical community.